- `3x-y = -8`
- `-9x+2y=18`

We need to eliminate either x or y to enable us to solve so multiply 1. by 2 so that we will have -2y:

`therefore 3. (times 2) 6x - 2y = -16` now add 2. to that

3. + 2. = 6x + (- 9x) and 2y + (- 2y) and that equals -16 + 18

`therefore -3x +0y= 2`

`therefore -3x=2`

`therefore x=2/-3`

Now substitute into one of your earlier equations (any one) to find y:

`3x - y = -8`

`therefore 3(-2/3) - y = -8`

`therefore-2 - y = -8`

`therefore -y= -8+2`

`therefore - y= -6`

`therefore y=6`

`(-2/3; 6)`

**Therefore x= -2/3 and y = 6 **

(1) 3x - y = -8

(2) -9x + 2y = 18

(1) x 2:

6x - 2y = -16

Add this to equation (2)

-3x = 2

Now its single variable and you can solve for x. Plug this back into one of the original equations and solve for y.

`3x-y=-8`

`-9x+2y=``18`

Multiply first for 3:

`9x-3y=-24`

add first to second:

`-9x+2y+9x-3y=18-24`

`-y=-6`

`y=6`

From first line:

`3x-6=-8`

`3x=-2` `x=-2/3`